Efficacy and safety of ormeloxifene in the management of dysfunctional uterine bleeding - Malik, Sabah; Musharaf, Saba; Malik, Fidah; Abass, Mohd (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: The term dysfunctional uterine bleeding (DUB) is used for abnormal uterine bleeding occurring in the absence of identifiable pathology. A number of drugs are available for management of DUB- nonsteroidal anti-inflammatory drugs, tranexamic acid, ethamsylate, hormones like Oral contraceptives progestins etc. The present study was done to determine the efficacy and safety of ormeloxifene in the management of DUB. Methods: This prospective clinical study involved 50 cases with DUB who were treated with ormeloxifene 60 mg tablet twice a week for first 12 weeks and the once a week for next 12 weeks. They were followed after 6 months of therapy. The outcome was studied by assessment of menstrual blood loss by PBAC score, Hb level in g/dl, endometrial thickness in mm, relief of dysmenorrheal and any side effects of drugs. Results: The median PBAC score was significantly reduced from 316 to 52 after 6 months of therapy. The mean Hb concentration was significantly increased from 7.8 g/dl to 9.1 g/dl at 6 months of therapy. The mean endometrial thickness was reduced from 10 mm to 7.9 mm after 6 months of therapy. 66% of women showed marked subjective improvement in symptoms. Amenorrhea was the main side effect (12%). Conclusions: Ormeloxifene has significant effect in reducing endometrial thickness, decreasing the amount of menstrual blood loss, reducing dysmenorrhea and thereby improving the general condition of the patient. It is definitely a better alternative to hysterectomy in women who wish to avoid surgeries and maintain their reproductive functions.